Municipal solid waste management : towards the realization of sustainable management in the context of Sri Lanka's Kandy municipal council - Bandusena, Kodagoda Withanage Harshani Chathurika; Mallak, Shadi Kafi; Abu Samah, Mohd Armi (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Over the past decade, generation of Municipal Solid Wastes (MSW) in Sri Lanka has increased due to rapid economic growth, industrial and urban development. Thus, the management of MSW in Sri Lanka can be considered relatively poor and inadequate. This study conducted, among residents and workplaces in the Kandy municipal council area. It proposes to study the knowledge, perception, and concern of the respondents. The questionnaires were distributed among 340 respondents. The findings of this study show that only 56.5% of respondents’ have proper knowledge of solid waste management practices. Basically, in at the same time, the results had been showed lack of perception and concern as percentage 59.8% and 60% among considered respondents. The results revealed that there is a lack of knowledge, perception, and concern of respondents towards municipal solid waste management. The study further provides potentials of MSW management system for sustainable environmental development in KMC.